2017
DOI: 10.1515/zfs-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Different sources of delay and acceleration in early child bilingualism

Abstract: Abstract:The present article argues that the two effects observed in bilingual first language acquisition, delay and acceleration, have different sources. Whereas delay can be due to cross-linguistic influence on the competence or the performance level and to the mere cognitive burden to process two languages, acceleration is always rooted in efficient computation in a non-linguistic sense. The evidence for the difference between delay and acceleration effects stems from children who are raised bilingually fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Studies comparing 2L1 children to monolingual children have generally found that simultaneous bilinguals were not disadvantaged, acquiring the two languages in a similar fashion and at a similar pace as their monolinguals peers (for an overview see Genesee and Nicoladis, 2007). Some studies reported specific acceleration effects, whereas other studies reported delays (see Hager and Müller, 2015, for a discussion of robust and non-robust domains in 2L1 children in comparison to monolingual children of the same language; see Müller, 2017, for a discussion of sources for acceleration and delay). Acceleration has been found for the area of morpho-syntax, with functional elements from the more developed language serving as a bootstrap for the acquisition of the functional elements of the other language (e.g., Gawlitzek-Maiwald and Tracy, 1996).…”
Section: Factors Influencing Child Bilingual Acquisitionmentioning
confidence: 99%
“…Studies comparing 2L1 children to monolingual children have generally found that simultaneous bilinguals were not disadvantaged, acquiring the two languages in a similar fashion and at a similar pace as their monolinguals peers (for an overview see Genesee and Nicoladis, 2007). Some studies reported specific acceleration effects, whereas other studies reported delays (see Hager and Müller, 2015, for a discussion of robust and non-robust domains in 2L1 children in comparison to monolingual children of the same language; see Müller, 2017, for a discussion of sources for acceleration and delay). Acceleration has been found for the area of morpho-syntax, with functional elements from the more developed language serving as a bootstrap for the acquisition of the functional elements of the other language (e.g., Gawlitzek-Maiwald and Tracy, 1996).…”
Section: Factors Influencing Child Bilingual Acquisitionmentioning
confidence: 99%
“…Instead, Müller [47] argues that sometimes bilinguals rely on domain-general mechanisms in response to superficial similarities in their two languages, and this is mischaracterized as acceleration (see also [48,49]). For example, bilingual learners of German in combination with a Romance language, such as Italian or French, tend to correctly place finite verbs in second position in German [50].…”
Section: Domain-general Accountsmentioning
confidence: 99%
“…Arnaus Arnaus , Müller (2017), Repetto and Müller (2010), and Schmeißer and Jansen (2016) have first indications from a cross-sectional study (only 18 of the 91 children were younger than 42 months, the age at which monolingual German children have acquired target-like word order) and eight longitudinal studies (1;6-3;6) that bilingual French/Italian/Spanish-German children are accelerated in finite-verb placement in German main clauses. German is a V2-language, in which any constituent (the subject, the object or a clause) appears in first position of main clauses, and the finite verb immediately follows it.…”
Section: Shared Structures As a Useful Concept?mentioning
confidence: 99%